Tissue lipidomic profiling supports a mechanistic role of the prostaglandin E2 pathway for albuminuria development in glomerular hyperfiltration - Kaiser-Graf, Debora; Schulz, Angela; Mangelsen, Eva; Rothe, Michael; Bolbrinker, Juliane; Kreutz, Reinhold (Frontiers in Network Physiology, 2023)
Background: Glomerular hyperfiltration (GH) is an important mechanism in the development of albuminuria in hypertension. The Munich Wistar Frömter (MWF) rat is a non-diabetic model of chronic kidney disease (CKD) with GH due to inherited low nephron number resulting in spontaneous albuminuria and podocyte injury. In MWF rats, we identified prostaglandin (PG) E2 (PGE2) signaling as a potential causative mechanism of albuminuria in GH.Method: For evaluation of the renal PGE2 metabolic pathway, time-course lipidomic analysis of PGE2 and its downstream metabolites 15-keto-PGE2 and 13-14-dihydro-15-keto-PGE2 was conducted in urine, plasma and kidney tissues of MWF rats and albuminuria-resistant spontaneously hypertensive rats (SHR) by liquid chromatography electrospray ionization tandem mass spectrometry (LC/ESI-MS/MS).Results: Lipidomic analysis revealed no dysregulation of plasma PGs over the time course of albuminuria development, while glomerular levels of PGE2 and 15-keto-PGE2 were significantly elevated in MWF compared to albuminuria-resistant SHR. Overall, averaged PGE2 levels in glomeruli were up to 150x higher than the corresponding 15-keto-PGE2 levels. Glomerular metabolic ratios of 15-hydroxyprostaglandin dehydrogenase (15-PGDH) were significantly lower, while metabolic ratios of prostaglandin reductases (PTGRs) were significantly higher in MWF rats with manifested albuminuria compared to SHR, respectively.Our data reveal glomerular dysregulation of the PGE2 metabolism in the development of albuminuria in GH, resulting at least partly from reduced PGE2 degradation. This study provides first insights into dynamic changes of the PGE2 pathway that support a role of glomerular PGE2 metabolism and signaling for early albuminuria manifestation in GH.